2014
DOI: 10.1371/journal.pone.0098893
|View full text |Cite
|
Sign up to set email alerts
|

Guanabenz Interferes with ER Stress and Exerts Protective Effects in Cardiac Myocytes

Abstract: Endoplasmic reticulum (ER) stress has been implicated in a variety of cardiovascular diseases. During ER stress, disruption of the complex of protein phosphatase 1 regulatory subunit 15A and catalytic subunit of protein phosphatase 1 by the small molecule guanabenz (antihypertensive, α2-adrenoceptor agonist) and subsequent inhibition of stress-induced dephosphorylation of eukaryotic translation initiation factor 2α (eIF2α) results in prolonged eIF2α phosphorylation, inhibition of protein synthesis and protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…Despite the established roles of ER stress-induced apoptosis of cardiomyocytes in H/R-injury [ 23 , 24 ], there is no report on the effects of lycopene on ER stress-induced injury in cardiomyocytes. Given the defined role of ER stress and the related pathological conditions of H/R-injury, we propose that in addition to triggering ER stress via disruption of protein proper folding, TG also propagates ER stress, which is supported by both previous reports [ 8 , 48 ] and our findings that TG treatment resulted in an increase in GRP78 and CHOP/GADD153 expression along with the rate of apoptosis. In our current study, we found that TG treatment could decrease the cell viability of cardiomyocytes which was similar to the H/R treatment.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the established roles of ER stress-induced apoptosis of cardiomyocytes in H/R-injury [ 23 , 24 ], there is no report on the effects of lycopene on ER stress-induced injury in cardiomyocytes. Given the defined role of ER stress and the related pathological conditions of H/R-injury, we propose that in addition to triggering ER stress via disruption of protein proper folding, TG also propagates ER stress, which is supported by both previous reports [ 8 , 48 ] and our findings that TG treatment resulted in an increase in GRP78 and CHOP/GADD153 expression along with the rate of apoptosis. In our current study, we found that TG treatment could decrease the cell viability of cardiomyocytes which was similar to the H/R treatment.…”
Section: Discussionsupporting
confidence: 89%
“…Regulated phosphorylation of eIF2α by the ER stress-activated protein kinase PERK modulates protein synthesis and couples the production of ER client proteins with the organelle's capacity to fold and process them [ 23 ]. Since phosphorylation of eIF2α has been shown to occur soon after ER-stress induction in PC12 cells [ 24 ], we studied PERK activation upon NLGN3 synthesis after 0, 4, 8, 12, 16, 24 and 48 h. We observed that p-eIF2α levels increased over time with a similar trend for the R451C and G221R mutant variants, whereas they remained unaltered for the WT protein ( Figure 4 A, upper panel). The increase in p-eIF2α was detectable after 4 h from NLGN3 induction and reached the highest peak at 12 h, with both mutant variants reaching significantly higher levels over the WT NLGN3 control ( Figure 4 A and Supplementary Figure S2A).…”
Section: Resultsmentioning
confidence: 86%
“…As a proof-of-concept specific modulators of PP1 (and PP2A) holoenzymes have been developed not only for the treatment of CVDs but also for the treatment of diabetes, Parkinson’s disease and drug addiction ( Uehata et al, 1997 ; Armstrong et al, 1998 ; McConnell and Wadzinski, 2009 ; Yger and Girault, 2011 ). Concrete examples are disruption of the PP1/GADD34 complex by salubrinal or guanabenz or I-1/I-2 overexpression in rodent/pig models of myocardial infarction ( Boyce et al, 2005 ; Tsaytler et al, 2011 ; Liu et al, 2012 ; Neuber et al, 2014 ). Moreover synthetic peptides containing the PP1c-binding motif (RVxF) have been successfully used to disrupt PP1 complexes in a neuronal and cardiac context, inducing beneficial effects on synaptic transmission and PLB phosphorylation ( Reither et al, 2013 ; Sotoud et al, 2015 ).…”
Section: Therapeutic Perspectivementioning
confidence: 99%